Recent advances in alcoholic hepatitis. Issue 2 (21st May 2019) - Veryan, Jennifer; Forrest, EH
Abstract : Alcoholic hepatitis (AH) is an acute deterioration in liver function seen in the context of prolonged excessive alcohol consumption and is characterised by the rapid onset of jaundice. The diagnosis of AH has been controversial for many years: it is now accepted that there are clear clinical criteria which can be used to diagnose AH without the need for a liver biopsy. Corticosteroids remain the only treatment proven to be effective in reducing short-term mortality in severe AH; abstinence from alcohol is the most important factor in determining long-term survival. It is recommended a trial of corticosteroid therapy is considered only in those patients with high baseline 'static' scores (Glasgow Alcoholic Hepatitis score and model for end-stage liver disease). Response to corticosteroid therapy should be assessed using a 'dynamic' score such as the Lille score at day 7, with corticosteroids continuing only in patients with a favourable score. Infection and acute kidney injury are associated with poorer outcomes in AH. Early screening for and treatment of infection is recommended with antibiotic therapy overlapping with any subsequent corticosteroid treatment. A biomarker which predicts benefit from corticosteroids at baseline would avoid a trial of therapy to determine response. More efficacious therapeutic options for AH patients are required with N-acetylcysteine, granulocyte colony stimulating factor, faecal microbiota transplantation and routine antibiotics showing promise, but adequate controlled trials are needed to confirm efficacy. Liver transplant has an emerging role for some patients with severe AH not responding to corticosteroids and is likely to become more acceptable with improved methods of patient selection.